(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
Today, in difficult economic conditions of political instability, demographic challenges, as well as the pursuit of sustainable development, have become particularly relevant. In such circumstances, the protection of motherhood and childhood is of particular importance, which is considered by the state as a strategically important investment in the country’s future. The active policy of the state in the field of support for motherhood and childhood is one of the priorities of social policy. The measures taken today do not provide a sufficient level of support, and it is necessary to study existing approaches to support motherhood and childhood for the availability of all necessary incentives and mechanisms to ensure a high standard of living for families in accordance with the real needs of the country’s population.